The Effects of Tai Chi Chuan Exercise Training on the Lower Extremities of Middle-Aged and Elderly - Bo-Jen Ko; Ting-Ting Lee; Tai-Yen Hsu; Chen-Fu Huang (Applied Sciences, 2022)
Background: It is known that lower-limb muscle strength is easily maintained in elderly people who practice Tai Chi, although it is necessary to maintain lower-limb muscle strength even as age increases in order to prevent falls. However, the effect of long-term Tai Chi practice and age on lower-limb ability is unclear in middle-aged and elderly people. This research was designed to compare lower-extremity parameters during a countermovement jump between middle-aged and elderly individuals who frequently practice Tai Chi Chuan and individuals in the general population who constituted the healthy group. Methods: There were four groups, and each group included 12 participants. Ten Vicon motion system infrared cameras and two Kistler force plates were used. The data were standardized and analysed using independent-measure two-way ANOVA. Results: The statistical results showed that there was no interaction between the age factor and exercise type factor. The statistics of age factor also showed that age may decrease the jump height (36.36%), peak knee power (24.74%) and peak ankle power (21%) during the take-off phase. In the exercise type factor, long-term Tai Chi training significantly increased the jump height (60%), peak knee moment (19.80%), peak ankle moment (8.06%), peak hip power (29.80%), peak knee power (31.23%) and peak ankle power (16.88%) during the take-off phase. Conclusion: This study shows that long-term Tai Chi training can slow ageing-related functional decline. According to the results of this study, middle-aged and elderly people are encouraged to regularly perform Tai Chi exercises to increase the strength of various muscle groups in the lower limbs and slow the lower-limb muscle changes caused by ageing.